ANALISIS KESALAHAN BERBAHASA PADA ANAK USIA BALITA BERDASARKAN TATARAN FONOLOGI - Roudhoh, Fajriniati Kulsum; Mustika, R Ika; Primandhika, Restu Bias (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This analysis was conducted to determine errors in the speech that came out of the child's speech tools. In teaching the first language, children are able to master the language by imitating what their mother said. Through imitating language activities, children are able to develop language and knowledge about the structure of the habitual patterns of the language they imitate. The research method used by researchers is descriptive qualitative. This research was conducted to determine language errors; the sample in this study were children under five, two years old and four years old. The results of this study are that there are errors in the speech of the children, such as in 2-year-olds the errors in their pronunciation are only pronouncing the ending words such as / cow / become / pi /, / horse / become / da /, / lizard / become / dal. /. In children aged 4 years, the language error in the utterance is a change in phonemes such as / c / to / t /, / g / to / d /, / k / to / t /, and so on. In the development process, the language errors in terms of speech are included in the analysis of language in phonology.